Aplikasi Lean Manufacturing Pada Proses Produksi Produk Sanitary untuk Peningkatan Efisiensi (Studi Kasus Perusahaan Keramik) - Ni Made Sudri; Mohammad Hardiyanto; Annuridya Rosyidta Pratiwi Octasylva; Kintan Salsabila (JURNAL ILMU PENGETAHUAN DAN TEKNOLOGI (IPTEK), 2021)
Increasing the efficiency of closet products in sanitary ceramic companies by implementing lean manufacturing to increase company competition. The identification of problems found waste in the process of making the closet, namely the dominant waste of inventory (21.81%), overproduction (20.21%), and motion (18.87%). Resolving the types of waste in order to increase the efficiency of the process, the process of mapping tools is carried out to determine the type of tools that are in accordance with the dominant problem, obtained are process activity mapping (PAM) and supply chain response matrix (SCRM). Proposals for improvements that can be made to increase process efficiency are the addition of operator aids for reducing waste motion, drying time efficiency by adding a drying device at the bottom of storage. Inventory waste can be minimized by implementing a warehouse system using the FIFO method and forecasting production targets to handle overproduction. The increase in process cycle efficiency (PCE) was obtained by 3.15%.